Investigating post-traumatic stress disorder (PTSD) and complex PTSD among people with self-reported depressive symptoms - Fung, Hong Wang; Chien, Wai Tong; Lam, Stanley Kam Ki; Ross, Colin A. (Frontiers in Psychiatry, 2022)
Background: Trauma has been increasingly linked to depression. Previous studies have suggested that comorbid post-traumatic stress disorder (PTSD) may be associated with poor outcomes in depression treatment. However, the prevalence and correlates of ICD-11 PTSD and complex PTSD (CPTSD) in people with depression remain unclear. Methods: This study examined the prevalence and correlates of ICD-11 PTSD and CPTSD in an online convenience sample of 410 adults from 18 different countries/regions who reported clinically significant levels of depressive symptoms (indicated by a Patient Health Questionnaire-9 score ≥10). Results: According to the International Trauma Questionnaire results, 62.68% of participants met the ICD-11 criteria for PTSD/CPTSD (5.6% PTSD, 57.1% CPTSD). Participants with CPTSD reported more types of trauma and higher levels of interpersonal stress than those without PTSD. Participants with CPTSD also reported higher levels of mental health problems, including depressive, dissociative and psychotic symptoms, than those without PTSD. Only disturbances in self-organization (DSO) symptoms but not classical PTSD symptoms had a significant relationship with depressive symptoms when other major variables (including trauma, interpersonal stress, and comorbid psychotic and dissociative symptoms) were controlled for. Conclusions: Trauma-related symptoms should be regularly screened for in clients who report depressive symptoms. Depressed clients who have comorbid trauma disorders have more trauma and interpersonal stress and exhibit more severe mental health problems. They may require specific trauma-focused interventions in addition to standard depression treatments. Keywords: Depression; Post-traumatic stress disorder (PTSD); Complex PTSD; Trauma; Mental health